Combined tumor genomic profiling and exome sequencing in a breast cancer family implicates ATM in tumorigenesis: A proof of principle study. Issue 11 (16th August 2017) - Bubien, Virginie; Bonnet, Françoise; Dupiot‐Chiron, Jennifer; Barouk‐Simonet, Emmanuelle; Jones, Natalie; de Reynies, Aurélien; MacGrogan, Gaëtan; Sevenet, Nicolas; Letouzé, Eric; Longy, Michel
Abstract: Familial breast cancers (BCs) account for 10%‐20% of all diagnosed BCs, yet only 20% of such tumors arise in the context of a germline mutation in known tumor suppressor genes such as BRCA1 or BRCA2 . The vast genetic heterogeneity which characterizes non BRCA1 and non BRCA2 (or BRCAx) families makes grouped studies impossible to perform. Next generation sequencing techniques, however, allow individual families to be studied to identify rare and or private mutations but the high number of genetic variants identified need to be sorted using pathogenicity or recurrence criteria. An additional sorting criterion may be represented by the identification of candidate regions defined by tumor genomic rearrangements. Indeed, comparative genomic hybridization (CGH) using single nucleotide polymorphism (SNP) arrays allows the detection of conserved ancestral haplotypes within recurrent regions of loss of heterozygosity, common to several familial tumors, which can highlight genomic loci harboring a germline mutation in cancer predisposition genes. The combination of both exome sequencing and SNP array‐CGH for a series of familial BC revealed a germline ATM mutation associated with a loss of the wild‐type allele in two BC from a BRCAx family. The analysis of additional breast tumors from ten BC families in which a germline ATM mutation had been identified revealed a high frequency of wild‐type allele loss. This result argues strongly in favor of the involvement of ATM in these tumors as a tumor suppressor gene and confirms that germline ATM mutations are involved in a subset of familial BC.